Faktor-Faktor Yang Mempengaruhi Penggunaan E-Wallet Sebagai Alat Pembayaran E-Commerce Pada Generasi Z di Singaraja - Rachel Hotmaria Pasaribu; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This research aims to examine the influence of perceived ease of use and perceived usefulness on the use of e-wallets as a payment tool for e-commerce among Generation Z in Singaraja, both partially and simultaneously. This type of research is descriptive quantitative. The population in this study consists of all Generation Z individuals residing in Singaraja. The sampling technique used in this study is purposive sampling, with sample selection based on certain criteria, namely, Generation Z in Singaraja who are already employed and use e-wallets as a payment tool for e-commerce, with a total sample size of 120 people. Data collection methods utilize questionnaires and are analyzed using multiple linear regression analysis. Hypothesis testing employs the t-test and F-test, processed with the aid of SPSS version 25. The research results show that (1) the perception of ease has a positive and significant effect on the use of e-wallets, (2) the perception of benefits has a positive and significant effect on the use of e-wallets, and (3) the perceptions of ease of use and benefits have a positive and significant effect on the use of e-wallets.